Deep Seated Density Anomalies Across the Iberia‐Africa Plate Boundary and Its Topographic Response. Issue 12 (11th December 2019) - Jiménez‐Munt, I.; Torne, M.; Fernàndez, M.; Vergés, J.; Kumar, A.; Carballo, A.; García‐Castellanos, D.
Abstract: The modes in which the lithosphere deforms during continental collision and the mechanisms involved are not well understood. While continental subduction and mantle delamination are often invoked in tectonophysical studies, these processes are difficult to be confirmed in more complex tectonic regions such as the Gibraltar Arc. We study the present‐day density and compositional structure of the lithosphere along a transect running from South Iberia to North Africa crossing the western Gibraltar Arc. This region is located in the westernmost continental segment of the African‐Eurasian plates, characterized by a diffuse transpressive plate boundary. An integrated and self‐consistent geophysical‐petrological methodology is used to model the lithosphere structure variations and the thermophysical properties of the upper mantle. The crustal structure is mainly constrained by seismic experiments and geological data, whereas the composition of the lithospheric mantle is constrained by xenolith data. The results show large lateral variations in the topography of the lithosphere‐asthenosphere boundary. We distinguish different chemical lithospheric mantle domains that reproduce the main trends of the geophysical observables and the modeled P and S wave seismic velocities. A sublithospheric body colder than the surrounding mantle is needed beneath the Betics‐Rif to adjust the measured potential fields. We link this body to the Iberian slab localized just to the east of the profile and having some effect on the geoid and Bouguer anomalies. Local isostasy allows explaining most of the topography, but an elastic thickness higher than 10 km is needed to explain local misfits between the Atlas and the Rif Mountains. Key Points: Lithosphere structure and upper mantle thermophysical properties in the Gibraltar Arc‐Atlas is obtained using an integrated geophysical‐petrological model A sublithospheric thermo‐compositional anomaly is found across the Iberia‐Africa plate boundary (Gibraltar) The thick lithosphere beneath the Betics and Rif tectonic domain, related to the W‐E slab, pulls down the topography about 1, 500 m